Research on Structural Similarity Design Emergency Exercise's Scenario. (11th February 2022) - Zhao, Kaigong; Wang, Haiyan; Zheng, Dengfeng
Abstract : In order to better apply the "situational response" model in the field of fluidized mining emergency management, it is the first step and the most critical problem to construct a reasonable scenario for fluidized mining emergency drills and reasonably put forward emergency management measures. Therefore, the structural similarity method is adopted in this paper to design emergency exercise scenarios. Firstly, a model of hierarchical structured scenarios is proposed, namely, modules of "Event-Environment-State of scenario-Disposal of task-Emergency action- Resources subject." Secondly, a scenario chain is designed, and a prediction method of the event development trend under the current scenario is proposed. Thirdly, the calculation method of scenario similarity and the proposed emergency response scheme method under the current situation after similarity comparison are proposed. Finally, the structural similarity analysis method is used to verify the application of "scenario construction" in oil and gas pipeline accidents, and better analysis results are obtained. Through this research, the application of "scenario design" in fluidized mining emergency management has been expanded and enriched, and technical support for "scenario design" of fluidized mining assisted decisions is provided.